Impact of Noise Pollution on the Hearing Capability of Industrial Workers in Lagos State, Southwest, Nigeria - A. S. Ogungbe; W. C. Amosu (Archives of Current Research International, 2017)
Noise induced hearing loss is a long known occupational hazard. The hearing loss is usually irreversible but preventable. The purpose of this study is to determine the impact of noise pollution on the hearing capability of industrial workers in Lagos State, Southwest, Nigeria. The study was carried out in the following industries: West African Gas Pipeline Company (WAPCo), Badagry; Niji-Lukas Engineering and Fabrication Firm, Isheri-Idimu; Beta Glass Company, Agbara; Alimoso Printing Press and Sawmill Factory, Ibereko - Badagry. Out of 105 subjects randomly selected by simple random sampling method, 100 subjects responded, which consist of Noise-exposed and Non-noise exposed, based on their noise exposure level in their work environment. Audiometric examination and noise mapping of the various departments in each industry were conducted. The data were analysed using Microsoft Excel spread sheets and IBM Statistical Package (SPSS) Software (Version 20.0) and the results are presented in percentage tables and multiple bar charts. Subjected inferential statistics for formulated hypotheses were analysed using Analysis of Variance (ANOVA), with 5% level of significance (P<0.05). The study showed that West African Gas Pipeline workers had a hearing threshold value of 23.68±5.27, which is on a close value with 22.29±4.92 of the control group (Non-noise exposed) and Alimoso Printing Press has 24.6±5.28, while Sawmill Factory workers, Beta Glass Industrial workers and Niji-Lukas Engineering Industry workers suffer mild noise induced hearing loss with 29.79±7.62, 30.18±8.27 and 41.5±6.4 threshold values respectively. The study also showed a poor usage of personal protective equipment by the workers in the industries; 68% of Sawmill Factory workers, 25% in Beta Glass Industry, 8% in WAPCo, 60% in Printing Press and 25% of Niji-Lukas workers do not use hearing protective device at all. This prevalence of occupational noise-induced hearing loss among the industrial workers is high due to exposure to high noise level above 85 dBA, poor usage of hearing protective device and a prolonged exposure to noise (10-12 hours per day).